Cross-cultural adaptation of the Beliefs about Medicines Questionnaire into Portuguese - Salgado, Teresa M. (2013)
CONTEXT AND OBJECTIVES The Beliefs about Medicines Questionnaire (BMQ-Specific) has proven useful for measuring patients' beliefs and associating them with non-adherence to treatment in several illness groups. The aim was to cross-culturally adapt the BMQ-Specific into Portuguese for the general population of medicine users. DESIGN AND SETTING Cross-sectional study conducted among users of public hospitals and outpatient clinics in Guarda and Covilhã, Portugal. METHODS The BMQ-Specific was translated using international recommendations for performing cross-cultural adaptation and was administered to 300 patients. An initial principal component analysis (PCA) was conducted with the extraction criterion of eigenvalue > 1.0, followed by a second PCA with restriction to two components. Reliability was assessed by calculating Cronbach's alpha coefficient. RESULTS The mean scores obtained for the Necessity and Concerns subscales of the Portuguese BMQ-Specific were 19.9 (standard deviation, SD = 2.8) (range 10 to 25) and 17.7 (SD = 3.9) (range 6 to 30), respectively. The first PCA produced an unstable three-component structure for the Portuguese BMQ-Specific. The final PCA solution yielded a two-component structure identical to the original English version (a five-item Necessity and a six-item Concerns subscale), and explained 44% of the variance. Cronbach's alpha for the complete Portuguese BMQ-Specific was 0.70, and 0.76 and 0.67 for the Necessity and Concerns subscales, respectively. CONCLUSION A cross-culturally adapted Portuguese version of the BMQ-Specific questionnaire for use among the general population of medicine users was obtained, presenting good internal consistency and component structure identical to the original English version.